Differences in the topographic profiles of retinal thickening in eyes with and without serous macular detachment associated with diabetic macular oedema. Issue 2 (13th November 2013) - Shereef, Hannah; Comyn, Oliver; Sivaprasad, Sobha; Hykin, Philip; Cheung, Gemmy; Narendran, Nirodhini; Yang, Yit Chiun
Abstract : Purpose: To investigate if cases of diabetic macular oedema (DMO) associated with serous macular detachment (SMD) have a different topographic profile of retinal thickening compared with DMO cases not associated with SMD. Methods: Optical coherence tomography scans of 152 eyes from 152 patients with centre-involving DMO and central subfield thickness >350 µm were identified. Measurements were taken of the neural retina at the highest point of thickening within the central subfield (H) and lateral extent of retina thicker than 350 µm (W). Group means were compared between eyes with SMD and eyes without SMD. Results: SMD was present in 55 eyes (36%). H was lower in eyes with SMD than in eyes without SMD (396 µm vs 550 µm, p<0.001) while W was higher in eyes with SMD compared with eyes without SMD (4.74 mm vs 4.18 mm, p=0.011). Conclusions: There were distinct differences in topographical profiles of retinal thickening between eyes with SMD and eyes without SMD. These findings suggest a possible mechanical basis for the pathogenesis of SMD in DMO.